Composition and the types of composition in terms of form and content - Sazan Raza Moen; Badrkhan Sulaiman Ali (Zanco Journal of Humanity Sciences)
This research is entitled "Composition and the types of composition in terms of form and content" which aimed to present the types and forms of composition, including writing and orally, as well as, to organize write expression, composition of the writing, methods of composition and the way of teaching. This is due to its scientific as like as other sciences, which is should depend on this subject for delivering their thought into society. Composition is considered as an important need within communication process in society, in terms of express their views, feelings, and opinions. For this reason, knowing the methods and styles of composition is an effective factor for everyone for passing his\her issue wherever. In other side, composition most important for linguistic teachers in regarding to study and research, especially in the field of Kurdish language and literature studies. In regarding to students, it is also important to them as key for learning and getting knowledge and taught of all subjects.